Parabolic Equation Accumulated Split Error and Its Correction Method for Tropospheric Radio Propagation - Peipei Wei; Xiaoyan Du; Xinwei Hu; Changyin Jiang (International Journal of Antennas and Propagation)
An increasingly popular approach of modeling electromagnetic wave propagation in the troposphere is to use the slip-step Fourier transform (SSFT) numerical algorithm to solve a parabolic equation (PE). However, available SSFT does not provide perfect solutions by introducing accumulated split error (ASE) for its step-by-step iteration process with a fixed propagation range step. The common analysis on one step split error is only a simple discussion on the split error of PE. Therefore, the main motivation of this study is to provide improvement on the accuracy of the PE by proposing an error correction method for the first time in the literature for PE. This method is on the basis of defining and deriving the accumulated split error. Its performance is then demonstrated with measured radar sea clutter data from Huanghai Sea, China.